Growth of Penaeus aztecus Ives, 1891 and Penaeus duorarum Burkenroad, 1931 in a hypersaline lagoon: relationships with environmental conditions and body size - Perez-Castaneda, Roberto; Sanchez-Martinez, Jesus Genaro; Luzvazquez-Sauceda, Maria de La; Rabago-Castro, Jaime Luis; Lpez-Rocha, Jorge Alberto; Benavides-Gonzalez, Flaviano; Blanco Martinez, Zeferino (Indian Journal of Fisheries, 2019)
Growth rates of the brown shrimp Penaeus aztecus Ives, 1891 and pink shrimp Penaeus duorarum Burkenroad, 1931 were estimated using length-frequency data in the hypersaline coastal lagoon, Laguna Madre of Tamaulipas, Mexico. The influence of environmental variables (salinity and temperature) and shrimp body size on the growth of both penaeid species were also evaluated. Shrimps were collected monthly from two fishing zones located at the central part of the lagoon throughout one year. A total of 4458 shrimps were analysed (69.3% P. aztecus and 30.7% P. duorarum) with total lengths (TL) ranging from 50.9 to 131.4 mm in P. aztecus and 59.7 to 134.5 mm in P. duorarum. Mean growth rate (±SD) of P. duorarum (3.10 ±1.78 mm TL per week) was slightly higher than that of P. aztecus (2.71 ±1.37 mm TL per week); however, the interspecific difference was not significant (p>0.05). Growth rates for both the penaeid shrimp species increased as water temperature increased. Additionally, a negative relationship between the growth rate and body length of shrimp was also detected suggesting that the positive effect of water temperature on the increase in shrimp length may be size-dependent. Keywords: Coastal lagoon, Laguna Madre, Penaeid, shrimp, Penaeus aztecus, Penaeus duorarum.